THE FOREIGN VESSEL SINKING POLICY IN ERADICATING ILLEGAL, UNREPORTED, AND UNREGULATED (IUU) FISHING IN THE INDONESIAN EXCLUSIVE ECONOMIC ZONE (IEEZ) - Richard Al Khalik (Student Journal of International Law, 2022)
This study aims to explain the relevancies regarding foreign vessel sinking policy to eradicate IUU fishing in IEEZ by national regulation to UNCLOS 1982. Another aim is to know the effectiveness of the foreign vessel sinking policy in eradicating IUU fishing in the IEEZ. This research is in the form of normative legal analysis. Legal research examines international conventions and national regulation provisions and their application to legal events. The data collection technique used is document study which includes international law regulations and national laws related to this thesis. The results indicate implementing the foreign vessel sinking policy is national law enforcement by Law No. 45 of 2009 amendment of Law No. 31 of 2004 Concerning Fishery in Article 69 (1) and (4). The foreign vessel sinking policy is not contrary to UNCLOS 1982 because the subject protected in EEZ by Article 73 (3) is the human being, not the vessel. It remains an effective means to create a deterrent effect as an optimum penalty.